Risk of suicide among U.S. veterans who deployed as part of Operation Enduring Freedom, Operation Iraqi Freedom, and Operation New Dawn - Bullman, Tim (Inj Epidemiol, 2021)
BACKGROUND: There has been concern about the risk of suicide among veterans returning from deployment to Afghanistan and Iraq as part of Operation Enduring Freedom, Operation Iraqi Freedom, and Operation New Dawn (OEF/OIF/OND). This study assessed suicide risk among OEF/OIF/OND veterans by gender and unit component. Firearm related suicide was also briefly examined. FINDINGS: The study cohort was identified from records of the US Department of Defense. Vital status and cause of death through 2016 was obtained from the Mortality Data Repository, which obtains data from the National Death Index. Suicide risk was first assessed using standardized mortality ratios (SMR)s, comparing the rate of suicide among all veterans, both collectively and separately by gender and unit component (active vs. reserve/National Guard) to the expected based on the US population adjusted for age, race, sex, and calendar year. Risk of suicide among active duty compared to reserve/National Guard veterans and male compared to female veterans was assessed with hazard ratios (HR) s, generated by Cox proportional hazards models, that included the covariates race, age, marital status, rank, and branch of service. There was an increased risk of suicide when all OEF/OIF/OND Veterans were compared to the US population, (SMR = 1.42; 95%, C.I., 1.38,1.46). Both male and female veterans had an increased risk of suicide when compared to their gender specific non-veteran counterparts, (SMR = 1.40; 95%, C.I., 1.36,1.45 and SMR = 1.85; 95%, C.I., 1.60,2.13), respectively. Active duty veterans had an increased risk of suicide compared to reserve/National Guard veterans, (HR = 1.22; 95%, C.I., 1.14,1.30). Male veterans had an almost 3-fold increased risk compared to female veterans, (HR = 2.85; 95%, C.I., 2.47,3.29). Among all veteran suicides 68.3% involved a firearm, including 68.7% among males and 59.5% among females. CONCLUSIONS: All OEF/OIF/OND veterans have an increased risk of suicide compared to non-veterans. Veterans will benefit from enhanced access to mental health services and initiatives to promote suicide prevention. Strategies that emphasize lethal means safety, an evidence based suicide prevention strategy which includes increasing safe storage practices (i.e., storing firearms unloaded and locked) can help address this increased risk of veteran suicide.